Scaling properties of dendrimers with long flexible branches - Ratner, M. (Functional Materials, 2007)
Monte-Carlo computer simulation as well as theoretical estimate of the properties of dendrimers with long, flexible branches in good solvent were conducted. It was shown that such dendrimers demonstrate universal behavior independent on details of their internal building. In particular, there exist a critical dendrimer generation number Gcr≈5 that signifies the transfer from coil-type structure with properties similar to linear polymer coil to fractal structure (with fractal dimension ε≈1.82). Numerical simulations as well as theoretical estimate shows that both Gcr and E (at G > Gcr) are independent on the number of spacers M in dendrimer branch and on dendrimer generation G (at G > Gcr).